2019
DOI: 10.1029/2018pa003507
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of Environmental Controls on Planktic Foraminifera Mg/Ca Using Global Core‐Top Data

Abstract: The Mg/Ca of planktic foraminifera is commonly assumed to be a univariate function of ocean temperature, but recent work suggests that nonthermal variables may have a secondary effect, thereby complicating an inverse approach for paleotemperature reconstructions. However, the significance of secondary variables has not been independently validated, and their inclusion may reflect statistical overfitting. Here we evaluate the significance of seven predictive variables on a global compilation (n = 1,124) of core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 109 publications
(291 reference statements)
0
29
0
Order By: Relevance
“…Our results show that the salinity effect on G. ruber (w) derived from core‐top samples is consistent with laboratory culture and sediment trap studies when using our new Mg/Ca data and varying habitat preference of foraminifera. Compared to a recent core‐top study based on compiled data set, where no significant salinity can be derived (Saenger & Evans, ), our calibrations based on one data set with nonenvironmental factors controlled seems to be better at resolving minor secondary influences. The small salinity effect on G. ruber (w) is corroborated by similar results obtained for T. sacculifer (w/o sac), which is evaluated from core‐top samples the first time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results show that the salinity effect on G. ruber (w) derived from core‐top samples is consistent with laboratory culture and sediment trap studies when using our new Mg/Ca data and varying habitat preference of foraminifera. Compared to a recent core‐top study based on compiled data set, where no significant salinity can be derived (Saenger & Evans, ), our calibrations based on one data set with nonenvironmental factors controlled seems to be better at resolving minor secondary influences. The small salinity effect on G. ruber (w) is corroborated by similar results obtained for T. sacculifer (w/o sac), which is evaluated from core‐top samples the first time.…”
Section: Discussionmentioning
confidence: 88%
“…Core‐top material provides the best analogue to downcore samples used for palaeoceanographic reconstructions; thus, establishing consistent salinity and pH effects across core‐top, laboratory culture, and sediment trap samples is critical to improve our confidence in the Mg/Ca proxy. Previous studies used compiled core‐top data to investigate secondary effects on planktonic Mg/Ca (Khider et al, ; Saenger & Evans, ). However, these studies based on compiled datasets have to consider nonenvironmental factors such as shell morphology, size fraction, and cleaning methods, which potentially compromise the capability of calibration models to resolve influences that are minor compared to that of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous calibrations for Mg/Ca have been based on laboratory culturing experiments (Gray & Evans, ; Lea et al, ; Nürnberg et al, ), sediment trap data (Anand et al, ; Gray et al, ), or modern core tops (Dekens et al, ; Elderfield & Ganssen, ; Khider et al, ; Saenger & Evans, ). Culture experiments provide precise constraints on environmental sensitivities but are limited in that laboratory conditions are not perfect analogs for the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has also recently been shown that the canonical ∼9% sensitivity of Mg/Ca to temperature may overestimate the pure thermal component (Gray & Evans, 2019). Several multivariate calibrations have been published (Gray & Evans, 2019; Khider et al., 2015; Saenger & Evans, 2019; Tierney et al., 2019). The implications of these other Mg/Ca calibrations are discussed in the supporting information, but do not change the main conclusions of this work (supporting information Text , Figure ).…”
Section: Methodsmentioning
confidence: 99%